Analysis of Potential Genes, Acute Phase Proteins and Hormonal Profiles Associated with Methicillin-Resistant Staphylococcus aureus (MRSA) Isolation from Pneumonic Sheep - Hanan M. Alharbi; Eman A. Noaman; Ahmed El-Sayed; Mohamed T. Ragab; Amani Hafez; Attia Eissa; Ahmed Ateya; Khairiah M. Alwutayd; Manal A. Babaker; Asmaa Darwish (Veterinary Sciences, 2025)
Staphylococcus aureus is a significant bacterial pathogen responsible for a wide range of diseases in both humans and animals. This study aimed to investigate nucleotide sequence variations, gene expression patterns, and serum biomarkers, including acute phase proteins (APPs), hormonal fluctuations, and iron profile parameters in sheep affected by pneumonia. Additionally, the study focused on the isolation and characterization of S. aureus from pneumonic sheep, with particular emphasis on the prevalence of methicillin-resistant S. aureus (MRSA) strains. Blood samples were collected from both healthy and pneumonic sheep for gene expression and biochemical analyses, while nasal swabs from pneumonic sheep were used for bacterial isolation and identification. Out of 100 nasal swabs analyzed, 44% tested positive for Staphylococcus spp., and 61.4% of these were confirmed as S. aureus by PCR. The mecA gene, a key marker of methicillin resistance, was identified in 17 isolates (38.6% of the S. aureus-positive samples). MRSA isolates showed complete resistance to amoxicillin, cloxacillin, and erythromycin, and high resistance to penicillin, amoxicillin, and tetracycline; however, all MRSA strains remained fully susceptible to vancomycin. Gene expression analysis revealed that TLR2, CLEC4E, PTX3, CXCL8, and IL15RA were significantly upregulated (p < 0.05) in pneumonic ewes, while SOCS3 expression was markedly downregulated. Sequence analysis of immune-related genes revealed notable nucleotide differences between healthy and affected animals. Furthermore, the pneumonic group exhibited significantly elevated levels of APPs, cortisol, and growth hormone, along with reduced levels of insulin, T3, and T4. These findings underscore the zoonotic risk posed by MRSA and emphasize the need for robust surveillance and antibiotic stewardship to control its spread. The study also highlights the importance of molecular diagnostics in accurately identifying MRSA and elucidating resistance mechanisms, thereby facilitating targeted treatment and informed management strategies.